2016
DOI: 10.1159/000445376
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relevance of Relative Maintenance of Maximal Eccentric Quadriceps Torque in Healthy Old Adults

Abstract: Background: Old referenced to young adults show a relative maintenance of maximal eccentric (RELM) compared to concentric muscle torque: ∼76 and ∼59%, respectively. However, it is unknown if RELM affords functional benefits in old adults. Objective: We examined if there is specificity between the two types of peak quadriceps torque (i.e., concentric and eccentric) and timed gait performance measured during level, ramp, and stair walking and if gait performance was higher in old adults with high versus low RELM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(108 reference statements)
1
2
0
Order By: Relevance
“…In partial agreement with previous studies, we observed a relative maintenance of maximal voluntary eccentric versus concentric muscle function for the knee extensors ( 23 , 26 ) but not the plantarflexors ( 24 ). Porter et al ( 24 ) also observed relative eccentric strength maintenance for the plantarflexors, but their sample included females only and older females tend to show a greater eccentric strength maintenance than older males ( 23 , 25 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In partial agreement with previous studies, we observed a relative maintenance of maximal voluntary eccentric versus concentric muscle function for the knee extensors ( 23 , 26 ) but not the plantarflexors ( 24 ). Porter et al ( 24 ) also observed relative eccentric strength maintenance for the plantarflexors, but their sample included females only and older females tend to show a greater eccentric strength maintenance than older males ( 23 , 25 ).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, older patients can improve their walking speed ( 36 , 37 ), fall risk ( 36 ), and balance ( 36 ) after eccentric muscle training. However, we previously ( 26 ) observed relatively weak associations between self-selected speed during downhill walking or stair decent and eccentric knee extensor strength in healthy older adults. As we elaborate below, our walking data provide important functional context for associations between the type of muscle action and walking condition, with implications for the prescription of targeted, muscle-specific exercise interventions for older adults.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation